Drivers of Change in Myanmar's Wild Elephant Distribution. (November 2016) - Songer, Melissa; Aung, Myint; Allendorf, Teri D.; Calabrese, Justin M.; Leimgruber, Peter
Myanmar is considered as a stronghold for wild elephants, though past estimates varied widely from 3, 000 to 10, 000. Results of a 2004 expert workshop showed estimates between 1, 430 and 2, 065. Building on surveys from 1990 to 1992, we conducted new expert interviews in townships throughout the range, with questions focusing on numbers of elephants living in townships and threats to and from elephants. We used general linear models to analyze characteristics of townships with and without elephants and to understand factors influencing changes in elephant presence. Our results show a major decrease in the geographic distribution of wild elephants in Myanmar between 1992 and 2006 with deforestation being the major driver. While forest cover is important for elephant presence, continuity with other elephant populations had a stonger influence on elephant persistence between surveys. Fragmentation of elephant populations is also a major driver of decline. Increases in forest cover increased elephant presence, while increases in edge and human population had the reverse effect. Deforestation and fragmentation lead to increased human–elephant conflict in some areas, sometimes concluding with the capture of elephants for timber operations and further draining wild populations. A national elephant action plan that includes monitoring of elephant status and threats is urgently needed and critical for Myanmar's wild elephants, particularly as more than 50 years of political isolation are rapidly ending and pressure on the country's natural resources is increasing exponentially.